2023
DOI: 10.3390/app13148095
|View full text |Cite
|
Sign up to set email alerts
|

Road Accident Hotspots on Jordan’s Highway Based on Geometric Designs Using Structural Equation Modeling

Abstract: One of the primary objectives of transportation engineering is to increase the safety of road infrastructure. This study seeks to determine the relationship between geometric design parameters in relation to road accident criteria based on accident hotspots on Jordan’s Desert Highway. The road accident data (from 2016 to 2019) were collected from the Jordan Traffic Department. The spatial pattern of hotspots was identified using a GIS tool named Getis-Ord Gi* based on the severity index of road accidents. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
(88 reference statements)
1
0
0
Order By: Relevance
“…Furthermore, we also determined highdensity regions to have high hotspot clustering, which demonstrates a positive relationship between the two. Our results are supported by past research, which also observed a high population to be linked with an increase in accident rates [49,64,65].…”
Section: Population Density Correlation and Hotspot Identificationsupporting
confidence: 92%
“…Furthermore, we also determined highdensity regions to have high hotspot clustering, which demonstrates a positive relationship between the two. Our results are supported by past research, which also observed a high population to be linked with an increase in accident rates [49,64,65].…”
Section: Population Density Correlation and Hotspot Identificationsupporting
confidence: 92%
“…Road-traffic accidents (RTAs) are widespread global hazards, influencing not only countries experiencing rapid urbanization and infrastructure development, but also those during the development phase. These accidents significantly affect roadway safety, sustainability and socio-economic development of countries (Aldala'in et al, 2023). In 2003, the worldwide economic impact of RTAs was estimated to be approximately $518 billion annually (Khasawneh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%